2022
DOI: 10.1007/s11548-022-02792-z
|View full text |Cite
|
Sign up to set email alerts
|

The colonoscopic vacuum model–simulating biomechanical restrictions to provide a realistic colonoscopy training environment

Abstract: Introduction Practicing endoscopic procedures is fundamental for the education of clinicians and the benefit of patients. Despite a diverse variety of model types, there is no system simulating anatomical restrictions and variations in a flexible and atraumatic way. Our goal was to develop and validate a new modelling approach for adhesion forces between colon and abdominal wall. Methods An inlay for a standard mechanical trainer was designed and 3D printe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Modelling the biomechanics of the living organism is crucial for the acceptance of ex vivo simulators [35]. They have been evaluated and thoroughly tested, including a randomized controlled trial, and found to be helpful in gaining experience, training, and even proficiency, irrespective of the level of experience at the start of the training [32,78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling the biomechanics of the living organism is crucial for the acceptance of ex vivo simulators [35]. They have been evaluated and thoroughly tested, including a randomized controlled trial, and found to be helpful in gaining experience, training, and even proficiency, irrespective of the level of experience at the start of the training [32,78].…”
Section: Discussionmentioning
confidence: 99%
“…Such a training opportunity contributes towards better training and aid in gaining experience that is required to adequately perform difficult tasks within a procedure [31]. Porcine-based endoscopy simulators have been created for endoscopic submucosal dissection [32], peroral endoscopic myectomy [33], anastomotic strictures in Crohn's disease [34], and colonoscopy [35]. Successful use of these simulators, however, requires that they adequately model the human patient and be consistent models, i.e., in a way that they always have similar tissue parameters and tissue properties.…”
Section: Introductionmentioning
confidence: 99%